1996
DOI: 10.3171/foc.1996.1.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Dual isotope single-photon emission computerized tomography used for prediction of histology and survival in patients after high-dose radiotherapy for malignant astrocytoma

Abstract: This study was conducted to determine the sensitivity of dual-isotope single-photon emission computerized tomography (SPECT) in predicting tumor recurrence and survival in patients treated with high-dose radiotherapy for malignant gliomas. Studies using SPECT with thallium-201 (Tl-201) and technetium-99m (Tc-99m) hexamethypropyleneamine oxime (HMPAO) in 50 consecutive patients with malignant astrocytomas treated by surgery and high-dose radiotherapy were performed 1 day before reoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…High-grade tumors have a higher thallium index than low-grade tumors. In a series of 15 biopsy-proven cases, Schwartz et al found an excellent correlation between imaging and histology (14/15 cases) using dual-isotope SPECT scanning with thallium-201 and 99mTc-HMPAO (27). Further study revealed a high thallium uptake in recurrent tumor and low thallium uptake in radiation necrosis.…”
Section: Figurementioning
confidence: 90%
“…High-grade tumors have a higher thallium index than low-grade tumors. In a series of 15 biopsy-proven cases, Schwartz et al found an excellent correlation between imaging and histology (14/15 cases) using dual-isotope SPECT scanning with thallium-201 and 99mTc-HMPAO (27). Further study revealed a high thallium uptake in recurrent tumor and low thallium uptake in radiation necrosis.…”
Section: Figurementioning
confidence: 90%
“…Differentiating between radiation necrosis and tumor progression is often difficult, and radioisotope brain scanning with thallium or position emission tomographic (PET) scanning may help in determining the pathologic basis of such reactions 52,53 . In some cases, a stereotactic biopsy may be required to establish the correct pathology, but our own experience in the radiosurgical treatment of primary malignant brain tumors indicates that most of what appears on scans to be radiation necrosis is actually a combination of necrotic tissue and viable tumor cells.…”
Section: Complications Of Gamma Knife Radiosurgerymentioning
confidence: 99%
“…Three years later a mass recurred, which was demonstrated to be active on SPECT scanning. (Dualisotope SPECT has been shown to be a reliable test for distinguishing recurrent tumor from radiation necrosis [58,71].) This resulted in stereotactic radiosurgery with the linear accelerator.…”
Section: High-grade Gliomasmentioning
confidence: 99%